Molecular analysis of ivy cells of the hippocampal CA1 stratum radiatum using spectral identification of immunofluorophores - Somogyi, Jozsef; Szabo, Andras; Somogyi, Peter; Lamsa, Karri P. (Frontiers in Neural Circuits, 2012)
Nitric oxide synthase-expressing (NOS+) GABAergic interneurons are common in hippocampal stratum radiatum, but these cells are less well characterised than NOS+ ivy cells in stratum pyramidale or neurogliaform cells in stratum lacunosum-moleculare. Here we have studied the laminar distribution of the axons and dendrites, and the immunoreactivity of these neurons recorded in rat hippocampal slices. We have used spectral analysis of antibody- or streptavidin conjugated fluorophores to improve recognition of genuine signals in reactions for molecules such as NOS and neuropeptide-Y, when immunolabelling was low in the recorded cell. We found that most NOS+ cells with soma in the CA1 area stratum radiatum exhibit characteristic properties of ivy cells; all tested cells were positive for NPY and negative for reelin. However, laminar distributions of their neurites differ from original characterization of ivy cells with the soma close to stratum pyramidale. Both their dendrites and axon are mainly in stratum radiatum and to a lesser extent in stratum oriens. In addition, both the dendrites and axons often extend to stratum lacunosum-moleculare. We conclude that ivy cells in stratum radiatum are predominantly feedforward inhibitory interneurons in the CA1 area, and their axonal output delivering GABA, NPY and NO can influence both the entorhinal cortex innervated and the CA3 innervated zones pre- and postsynaptically. Spectral analysis of fluorophores provides an objective algorithm to analyze signals in immunoreactions for neurochemical markers.